Da shu ju xiang mu guan li cong gui hua dao shi xian = Foundations for architecting data solutions : managing successful data projects / = Foundations for architecting data solutions : - Malaska, Ted; Seidman, Jonathan (Tu ling cheng xu she ji cong shu, 2020)
Detailed summary in vernacular field.